SIMULTANEOUS MEASUREMENT OF SYN-GAS COMPONENT (H2, CO2, CH4, AND CO) AS PRODUCT OF BIOMASS GASIFICATION BY USING VALIDATED GC-TCD METHOD - Muhammad Rizky Mulyana; Oman Zuas; Harry Budiman; Sabar Simanungkalit; Nino Rinaldi (Testing Center for Oil and Gas LEMIGAS, 2018)
Biomass gasification has been widely known method to produce syn-gases, which can be considered as great alternative substitution for fossil fuels. However, accurate verification of the syn-gas composition requires a reliable and validated method for simultaneous measurement of H2, CO2, CH4, and CO. In order to fulfill the aforementioned requirements, which is the objective of this study; a GC-TCD method for simultaneous measurement of H2, CO2, CH4, and CO component in syn-gas has been validated in accordance to ISO/IEC 17025 and its application for real samples. For the method validation purpose, all of the performance parameters were evaluated and discussed in detail in this study. Intraday precision and interday precision were found to be acceptable having the %RSD below 0.67xCV Horwitz and below 1.0xCV Horwitz, respectively. The bias value falls within +2σ for entire components, indicating that the method accuracy can be accepted. Coefficient correlation for all components was higher than 0.99, which means that the method has suffi cient linearity. LoD and LoQ for each component were found to be lower than typical syn-gas concentration range. The method roughness was also found in an acceptable level (the p-values was higher than 0.05 for allctarget components. Application of the validated method for the measurement of a real syn-gas samples indicated that the method is quite reliable to produce an accurate data and the validated methid can be used in a routine analysis. The innovation of this study, as shown by experiment results, is to evaluate the validated method’s performance for simultaneous determination of syn-gas components’ concentration in one channel, compared to common method in which the syn-gas components were measured separatedly in a different channel.Biomass gasifi cation has been widely known method to produce syn-gases, which can be consideredas great alternative substitution for fossil fuels. However, accurate verifi cation of the syn-gas compositionrequires a reliable and validated method for simultaneous measurement of H2, CO2, CH4, and CO. Inorder to fulfi ll the aforementioned requirements, which is the objective of this study; a GC-TCD methodfor simultaneous measurement of H2, CO2, CH4, and CO component in syn-gas has been validated inaccordance to ISO/IEC 17025 and its application for real samples. For the method validation purpose,all of the performance parameters were evaluated and discussed in detail in this study. Intraday precisionand interday precision were found to be acceptable having the %RSD below 0.67xCV Horwitz and below1.0xCV Horwitz, respectively. The bias value falls within +2σ for entire components, indicating that themethod accuracy can be accepted. Coeffi cient correlation for all components was higher than 0.99, whichmeans that the method has suffi cient linearity. LoD and LoQ for each component were found to be lowerthan typical syn-gas concentration range. The method roughness was also found in an acceptable level(the p-values was higher than 0.05 for allctarget components. Application of the validated method for themeasurement of a real syn-gas samples indicated that the method is quite reliable to produce an accuratedata and the validated methid can be used in a routine analysis. The innovation of this study, as shown byexperiment results, is to evaluate the validated method’s performance for simultaneous determination ofsyn-gas components’ concentration in one channel, compared to common method in which the syn-gascomponents were measured separatedly in a different channel.Keywords: syn-gas, GC-TCD, method validation.